Analisa Kekasaran Permukaan Pada Proses Pembubutan Material AISI 4140 dengan Nose Radius dan Cutting Parameter yang Berbeda - Masrufaiyah; Sugeng Hariyadi; Mochammad Miftahurrohman (Wahana Teknik, 2020)
The process of machining the shaft can be done using a lathe where it is often obtained that the surface roughness value is not as desired. This is influenced by several factors including the nose radius on the tool geometry and cutting parameters. To determine the effect of these two factors, this study used AISI 4140 material with a WNMG Sumitomo type carbide chisel with a nose radius R 04 and R 08 as well as different feeding starting from F 70, F 80, F 90, F 100, F 110 and F 120 and using the same Rpm, Rpm 900. The results show that to achieve a roughness value of N8 with a roughness value of 3.2 m, a tolerance of 2.4 m–4.8 m, the tool radius and feeding used include: R 04 with F 70 with a value of 3.101 m, R 04 with F 80 with a value of 4.050 m, R 08 with F 90 with a value of 2.562 m, R 08 with F 100 with a value of 3.164 m, R 08 with F 110 with a value of 3.828 m, R 08 with F 120 with a value of 4,556 m. Based on the roughness value (Ra), the larger the nose radius used, the lower the roughness value obtained. The more nose radius used, the higher the roughness value obtained. Keywords: AISI 4140, Cutting, Nose, Parameter, Radius, Roughness, Surface.